2020
DOI: 10.3390/cells9081864
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Treatment of Colorectal Cancer Cell Lines Alters DNA Methylation, DNA Repair and Tumor Progression-Related Gene Expression

Abstract: Global DNA hypomethylation is a characteristic feature of colorectal carcinoma (CRC). The tumor inhibitory effect of S-adenosylmethionine (SAM) methyl donor has been described in certain cancers including CRC. However, the molecular impact of SAM treatment on CRC cell lines with distinct genetic features has not been evaluated comprehensively. HT-29 and SW480 cells were treated with 0.5 and 1 mmol/L SAM for 48 h followed by cell proliferation measurements, whole-genome transcriptome and methylome analyses, DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…In addition, at pharmacological doses AdoMet has an excellent tolerability record without side effects [ 16 , 17 ]. Notably, in the last decade many in vitro and in vivo studies have shown promising anti-cancer properties of AdoMet, and growing scientific interest is now focusing on identifying the biological mechanisms and signal transduction pathways related to the antitumoral activity of this physiological compound [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at pharmacological doses AdoMet has an excellent tolerability record without side effects [ 16 , 17 ]. Notably, in the last decade many in vitro and in vivo studies have shown promising anti-cancer properties of AdoMet, and growing scientific interest is now focusing on identifying the biological mechanisms and signal transduction pathways related to the antitumoral activity of this physiological compound [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor effect of AdoMet on different types of human cancer has been widely reported in the literature, and its association with other anticancer molecules has identified the sulfonium compound as a promising biomolecule for combined anticancer therapies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Adomet-regulated Ncrnas In Human Cancer and Their Role In Chemotherapymentioning
confidence: 99%
“…Furthermore, the sulfonium compound has been shown to increase serotonin levels in the brain, similar to antidepressant drugs, but with fewer side effects [21], and clinical studies have demonstrated that AdoMet is equally effective in reducing joint pain and inflammation as nonsteroidal anti-inflammatory drugs [22]. More recently, the antiproliferative properties of AdoMet and its implication in multiple cellular processes such as proliferation, differentiation, cell cycle regulation and apoptosis in various tumor cells have been thoroughly examined in the literature [28][29][30][31][32][33][34][35][36][37][38]. It has been shown that in human osteosarcoma U2OS and LM-7 cells, treatment with AdoMet leads to a dose-dependent decrease in cell proliferation and induces the onset of apoptosis [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence accumulating in literature in recent years on the antiproliferative and proapoptotic activities exerted by AdoMet in colon cancer cells highlighted the pleiotropic effects of this eclectic multi-target sulfonium compound, evidencing its ability to modulate the genes responsible for cell invasion and metastasis [16][17][18][19][20][21][22]. In RKO and HT-29 colon cancer cells, AdoMet induced apoptosis by decreasing the expression of the gene encoding FLICE-like inhibitory protein, leading to caspase 8 activation and the consequent release of cytochrome c from the mitochondria [17].…”
Section: Introductionmentioning
confidence: 99%